2020
DOI: 10.5751/es-11508-250216
|View full text |Cite
|
Sign up to set email alerts
|

A comparative framework to support an ecosystem approach to fisheries in a global context

Abstract: Although an ecosystem approach to fisheries has been recognized as a means of progressing toward sustainable fishing, successful implementation of this approach has been limited. However, one way in which progress has been made is through the use of suites of indicators. Decision tree frameworks can be used to incorporate trends in ecological, fishing, and environmental indicators into ecosystem assessments. A relatively generic decision tree framework has been developed and successfully applied to multiple ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…In line with findings in the above research streams, stakeholder engagement has been found to have positive effects both on improving ecosystem-based management and assessments (Adams et al, 2014;Dutra et al, 2015;Lockerbie et al, 2020) and on MSP processes (Frazão Santos et al, 2021). This ranges from engaging managers and policymakers (Dutra et al, 2015) to academic communities (Adams et al, 2014) and accounting for expert knowledge (Lockerbie et al, 2020).…”
Section: "Coastal and Marine Management" Research Streamsupporting
confidence: 63%
“…In line with findings in the above research streams, stakeholder engagement has been found to have positive effects both on improving ecosystem-based management and assessments (Adams et al, 2014;Dutra et al, 2015;Lockerbie et al, 2020) and on MSP processes (Frazão Santos et al, 2021). This ranges from engaging managers and policymakers (Dutra et al, 2015) to academic communities (Adams et al, 2014) and accounting for expert knowledge (Lockerbie et al, 2020).…”
Section: "Coastal and Marine Management" Research Streamsupporting
confidence: 63%
“…Other methods to consider for assessing the overall condition of ecosystems include the use of decision‐trees (Lockerbie et al, 2020) or disaggregated assessments such as those conducted for the IndiSeas project (Lockerbie et al, 2016; Shin et al, 2010) or the Ocean Health Index (OHI) (Halpern, 2020; Halpern et al, 2012), where different elements of the ecosystem are retained so that multiple objectives are being considered. A similar approach is followed for assessments under OSPAR, which facilitates implementation of the EU MSFD, where condition reports are grouped according to indicator types or themes, in separate outputs (Greenstreet et al, 2011; Heslenfeld & Enserink, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Other methods to consider for assessing the overall condition of ecosystems include the use of decision-trees (Lockerbie et al, 2020) or disaggregated assessments such as those conducted for the IndiSeas project (Lockerbie et al, 2016;Shin et al, 2010) or the Ocean Health Index (OHI) (Halpern, 2020;Halpern et al, 2012),…”
Section: Integrated Ecosystem Assessmentmentioning
confidence: 99%
“…The doughnut approach is a flexible non-sectorial specific framework that can be used in the different blue economy activities supporting multi-sectorial discussion processes. It provides a holistic view of the analyzed sector and the ecosystem where it interacts, and adds to other already existing specific sectorial holistic indicator approaches, such as, for example, in the fisheries case Anderson et al (2015) or Carpenter et al (2021), and those linked with ecosystem fisheries assessments , Kleisner et al 2013, Fu et al 2019, Lockerbie et al 2020, or the information provided regularly in specific reports by institutions such as the STECF.…”
Section: Fisheries Transitionmentioning
confidence: 99%